Estimating the impact of forest use on biodiversity in protected areas of developing tropical regions - Faude, Ulrike; Feilhauer, Hannes; Schmidtlein, Sebastian (Erdkunde, 2010)
Summary: In many developing tropical regions, especially indigenous people are often deprived of their traditional land use rights due to the establishment of protected areas. This conservation practice jeopardizes people's livelihoods and ultimately counteracts conservation efforts by provoking illegal use of natural resources. Thus, approaches that consider local livelihood needs in conservation planning are of high importance. In this regard, methods to quantify human impact on conservation-relevant biodiversity features, e.g., species richness, are required to objectively evaluate the effectiveness of current management practices and to facilitate tradeoffs between land use and nature conservation. We introduce an approach that draws on the degree of human-induced forest fragmentation as a proxy for land use intensity. Quantitative information on forest fragmentation was obtained by applying landscape metrics on satellite imagery. We analyzed relations between this proxy and vascular plant species data from an Indian protected area. In our case, species richness on a local scale was only marginally affected by forest fragmentation. However, ongoing land use throughout the reserve resulted in distinct alterations of species composition and promotion of biological invasion.
Keywords: Conservation; Forest fragmentation; Indigenous people; Land use; Landscape metrics; Protected area; Species composition; Species richness